Aktivitas Antagonistik Endofit Fusarium solani EnI dari Bunga Bawang Dayak terhadap Aspergillus flavus, Kontaminan dari Kacang Kedelai: Antagonistic Activities of Endophytic F. solani EnI from Eleutherine palmifolia Flower againts Aspergillus flavus, Contaminants from Soybean - Noorkomala Sari; Akhmad Rizali; Noor Laili Aziza (Median : Jurnal Ilmu Ilmu Eksakta, 2022)
Endophytic fungi are one of the biological control agents whose ability has recently been reported to protect plants from environmental stress, both pests, and diseases. The endophytic fungus Fusarium solani EnI has been isolated from the flowers of the Dayak onion medicinal plant in the wetland environment of South Kalimantan, which can be used as agent biological control to plant pathogen. This study to determine the antagonism ability of the endophytic fungus from Dayak onion flower, F. solani EnI against Aspergillus flavus which contaminates soybeans. Parameters observed in this study, the inhibition of endophytic fungi to F. solani En1 using the dual culture method. The results showed a variation in the percentage of inhibition of the endophytic fungus F. solani EnI against the contaminant fungus A. flavus soybean in vitro on three culture media, which are PDA is 36.67%, soybean media is 31.19%, and corn media is 25%.